Efficacy of two-step resilience-oriented intervention for veterans with a remote traumatic brain injury - Assonov , Dmytro (The Ukrainian Scientific Medical Youth Journal, 2022)
Researchers argue that rehabilitation interventions which cultivate resilience may potentiate the effect of standard treatment and promote the readaptation of veterans with traumatic brain injury. At the same there is a lack of such interventions. The objective of the article was to investigate the efficacy of two-step resilience-oriented intervention for veterans with traumatic brain injury in remote period. We hypothesized that, compared with patients who received standardized treatment and rehabilitation in inpatient setting, those who received standardized treatment plus TROI would report increase in resilience effectiveness and positive outcomes, as well as reduced clinical symptoms. A total of 146 veterans with traumatic brain injury were enrolled into a randomized controlled trial either into intervention group, which received two-step resilience-oriented intervention and standard treatment and rehabilitation or to control group, which received only standard treatment and rehabilitation. Psychometric measures were administered at baseline, post-treatment, and 3 months follow-up. Connor-Davidson Resilience Scale (CD-RISC), Neurobehavioral Symptom Inventory (NSI), Montreal Cognitive Assessment Scale (MoCA), Hospital Anxiety and Depression Scale (HADS), Positive and Negative Affect Scale (PANAS), Posttraumatic Stress Disorder Checklist 5 (PCL-5), Chaban Quality of Life Scale (CQLS) were used to assess the treatment effectiveness. A linear mixed effect modelling was used to model each outcome. Improvements in all outcomes at post-treatment were observed in both intervention and TAU groups. After adjusting for the baseline cognitive performance, gender, brain injury clinical type and time since last trauma, the intervention group demonstrated more favorable score on CD-RISC, MoCA, PCL-5, PANAS while demonstrating no clinically significant improvement in NSI, HADS and CQLS at both post-treatment and follow-up. Difference between groups in resilience-related outcomes like positive affect and quality of life only increased throughout time, making a good follow-up prognosis. In summary, targeting cognitive and emotional factors in a single psychological intervention improves the resilience in veterans with traumatic brain injury, making veterans more adaptable and more effective in managing both persistent clinical symptoms and comorbid post-traumatic stress. Adding such resilience-oriented program to the standard inpatient treatment and rehabilitation provides improvement in clinical outcomes and better prognoses than just following usual treatment strategies.